2007
DOI: 10.1021/cm062984i
|View full text |Cite
|
Sign up to set email alerts
|

Silica−Polyamine-Based Carbon Composite Adsorbents as Media for Effective Hydrogen Sulfide Adsorption/Oxidation

Abstract: New silica-carbon adsorbents were prepared by pyrolysis of silica-polyamine composites at 600 °C. The heat treatment was expected to activate nitrogen for effective hydrogen sulfide oxidation. Moreover, the same pyrolysis treatment was applied on silica-polyamine adsorbents previously used to remove copper ions for aqueous solution. The performance of these materials as H 2 S adsorbents was tested using a home-developed dynamic breakthrough test. Samples from before and after the adsorption process were charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…[42] These studies required thermal stability of the SPCs and this has been confirmed by DTG analysis. [43] In addition, a series of luminescent ruthenium complexes with various types of ligands have also been successfully immobilized on SPC. [14] Given the ease of modification of the SPC amine surface with aromatic ligands using the Mannich Reaction without prior parasubstitution, [38,44] and its ability to provide a basic surface for bifunctional catalysis, SPC would appear to be a suitable candidate for the immobilization of metal pincer complexes.…”
Section: Scheme 2 Synthesis Of Silica Polyamine Compositesmentioning
confidence: 99%
“…[42] These studies required thermal stability of the SPCs and this has been confirmed by DTG analysis. [43] In addition, a series of luminescent ruthenium complexes with various types of ligands have also been successfully immobilized on SPC. [14] Given the ease of modification of the SPC amine surface with aromatic ligands using the Mannich Reaction without prior parasubstitution, [38,44] and its ability to provide a basic surface for bifunctional catalysis, SPC would appear to be a suitable candidate for the immobilization of metal pincer complexes.…”
Section: Scheme 2 Synthesis Of Silica Polyamine Compositesmentioning
confidence: 99%
“…Our initial investigations began in the early 1990's and focused on developing a metal remediation technology that was capable of being commercialized using the SPC platform. Eventually, this surface was expanded to a wider range of applications and synthetic approaches . The early years focused on the synthesis and applications of the polyamine‐amorphous silica gel composites to problems in heavy metal ion removal and recovery .…”
Section: Introductionmentioning
confidence: 99%
“…The early years focused on the synthesis and applications of the polyamine‐amorphous silica gel composites to problems in heavy metal ion removal and recovery . Later characterization of the polymer‐surface interface and refining the use of polymer modifying ligands to improve metal selectivity was the focus of the research . Most recently, the emphasis has been on the synthesis of these composites by more environmentally benign routes, the development of materials that can capture anions as well as cations and to their applications in catalysis .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the elastic nature of polymer matrices limits their use in packed column systems, because the frequent swings between shrinking and swelling during the adsorptionregeneration cycles can lead to a short lifetime and increase the requirement of dead volume in plant design. Recently, the Rosenberg Group reported the synthesis of hydrophilic silica-polyallylamine composites (SPC) and their application for removing toxic metal cations, such as Cu 2+ and Ni 2+ [7][8][9]. The use of SPC as adsorbent matrices for the removal of hazardous anions and non-ions, however, has not been explored.…”
Section: Introductionmentioning
confidence: 99%